Occurrence and partition of organochlorine pesticides (OCPs) in water, sediment, and organisms from the eastern sea area of Shandong Peninsula, Yellow Sea, China. (January 2021) - Li, Huaxin; Jiang, Weiwei; Pan, Yulong; Li, Fujuan; Wang, Chunhui; Tian, Hua
Abstract: To evaluate the occurrence and partition of organochlorine pesticides (OCPs), hexachlorocyclohexanes (HCHs) and dichlorodiphenyltrichloroethanes (DDTs), water, sediment, and organisms were sampled from the eastern sea area of Shandong Peninsula (Yellow Sea, China) across all four seasons in 2016. There were three OCP hotspots in the sediment, mainly caused by the transportation of lindane and dicofol from adjacent Swan Lake and Guhe River. Waterborne OCP levels were highest in winter and lowest in spring, without vertical variability, suggesting that the Yellow Sea Cold Water Mass was governing the spatio-temporal distribution of OCPs in seawater. There was substantial accumulation of HCHs and DDTs in organisms via sediment, as indicated by the relatively low fraction of sedimental fugacity, high bio-sediment accumulation factor, and a positive linear correlation between logΣHCHs and trophic level. This is the first study that has focused on the accumulation of OCPs in entire sediment-seawater-organism system involving multi-phyla of species. Graphical abstract: Unlabelled Image Highlights: There were three OCP hotspots in the sediment. There was substantial accumulation of OCPs in organisms via sediment. We detected a positive linear correlation between logΣHCHs and trophic level. This study focused on the accumulation of OCPs in entire sediment-seawater-organism.